Compósitos de polietileno de alta densidade (PEAD) com alto teor de resíduos de fibras de sisal via mistura termocinética - Laia, Melina Gonçalves Chagas de (2022)
Plant fiber reinforced polymer composites are receiving great attention as innovative materials for industrial applications in various sectors. The formulation of thermoplastic composites, with high levels of plant fibers via a high-intensity thermokinetic mixer, has been shown to be effective, obtaining composites with good properties. This work aimed to study high density polyethylene (HDPE) composites with high levels of sisal fibers (Agave sisalana), with and without coupling agent. Composites were prepared in different compositions in relation to fiber content, with 40, 50, 60 and 70% w/w, formulated via thermokinetic mixer and molded by compression. The bending mechanical properties, impact, morphology via scanning electron microscopy, thermal properties and water absorption were evaluated as well. The water absorption varied between 2 and 17.6%, increasing with fiber content. The flexural strength and flexural modulus reached 29.1 MPa and 3.8 GPa, respectively. The impact strength of the composites reached up to 76.6 J.m-1. SEBS-g-MA proving to be effective, not only as a compatibilizer, but also as impact modifier, increasing impact strength in all formulations in which they were present. This work demonstrates that HDPE composites with high contents of sisal fibers obtained via thermokinetic mixer have showed properties that are comparable with WPC (wood plastic composites), MDF (medium density fiberboard) and other materials that have similar applications. The formulation with 70% w/w together with 5% of SEBS-g-MA is promising, as it has presented an elastic modulus of 2.0 GPa, impact resistance of 65 J.m-1, water absorption of 17.6%, density of 0.91 g.cm-³ and flexural strength of 29.1 MPa, which is higher than the recommended by norm for MDF (23 MPa).